PELATIHAN EDITING FOTO SEBAGAI PENINGKATAN KOMPETENSI DAN SOLUSI MINAT SEKOLAH PADA PONPES MODERN ANNIDA - Rosandy, Triowali Rosandy; Handayani, Retno Dwi; Setiawati , Melia Grifin; Aglasia, Adimas; Septiawan, Yuda (LPPM Universitas Bina Bangsa, 2025)
The Modern Annida Islamic Boarding School is one of the pesantren located in South Lampung Regency. The teaching and learning process in this pesantren integrates the national curriculum with additional religious studies. However, at the Modern Annida Islamic Boarding School, the interest of students at the senior high school (SMA) level remains lower than that of students at the junior high school (SMP) level. Senior high school students are perceived as lacking sufficient competencies to be workforce-ready. Digital Graphic Design is a form of visual communication that presents information, products, or services through digital interfaces. Simply put, digital graphic design is specifically created for use on computers. Several methods can be applied to train students in digital graphic design at schools, including discussions, demonstrations, experiments, problem-solving, and lectures. By utilizing a Digital Graphic Design approach, the aim is to make education at the senior high school level in the Modern Annida Islamic Boarding School more engaging and less monotonous, with the hope that junior high school students will be encouraged to continue their education at the senior high school level within the institution. In this training, students are not only introduced to basic photo editing techniques using Adobe Photoshop but are also encouraged to develop creativity, which is highly essential in today's digital era. This program successfully sparked the students' interest in exploring their talents in graphic design, which could potentially become a source of income in the future.